The Power of Circles : a Guide to Building Peaceful, Just, and Productive Communities--One Circle at a Time. - Lavery, Norman G. (Wipf and Stock Publishers, 2016)
Communication is the key to all successful human interactions. In light of the expanding use of texting and other forms of electronic communication, we risk losing the personal, face-to-face meetings that have been the mainstay of positive relationships between individuals and groups for thousands of years. Lavery shows how the circle process is a powerful tool for overcoming this worrisome situation, as it offers a way to enhance communications, build and rebuild relationships, and improve problem-solving capabilities within families, neighborhoods, schools, corporations, and civic organizatio.